2018
DOI: 10.2147/tcrm.s160760
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of pregnancy with or without lupus nephritis: a systematic review and meta-analysis

Abstract: BackgroundAlthough it is well established that systemic lupus erythematosus (SLE) negatively affects pregnancy outcomes, there is insufficient evidence on the effect of lupus nephritis (LN) on antenatal management and pregnancy outcomes. We performed a systematic review and meta-analysis to determine the association of LN with management and pregnancy outcomes in SLE patients.MethodsEmbase, Medline, Cochrane, and ClinicalTrials.gov were carefully searched for relevant English and Chinese language studies. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
(70 reference statements)
3
30
1
3
Order By: Relevance
“…Women with SLE are receiving better multidisciplinary antenatal care ensuring better pregnancy outcome with the development of medicine. Nevertheless, current studies [5, 2325] also reported that SLE was associated with APOs including pre-eclampsia, pregnancy-induced hypertension, spontaneous abortion. The present study have synthesized current published studies regarding GDM and SLE, and the results indicated that SLE with not associated with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Women with SLE are receiving better multidisciplinary antenatal care ensuring better pregnancy outcome with the development of medicine. Nevertheless, current studies [5, 2325] also reported that SLE was associated with APOs including pre-eclampsia, pregnancy-induced hypertension, spontaneous abortion. The present study have synthesized current published studies regarding GDM and SLE, and the results indicated that SLE with not associated with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Among the immunologic diseases, systemic lupus erythematosus (SLE) principally affects women of childbearing age, and is the most recognized risk factor for the hypertensive disorders of pregnancy and p-AKI [ 128 , 129 , 130 , 131 ].…”
Section: The Role Of Immunologic Diseases In the Pathogenesis Of Tmentioning
confidence: 99%
“…1,2 Preeclampsia is a complication more frequently observed in women with SLE compared with healthy women, especially in those with lupus nephritis (with a 2 to 4 times higher risk). [2][3][4][5] In retrospective, prospective or population-based studies, preeclampsia has been reported between 10% and 30% of pregnancies in SLE patients. [6][7][8][9][10][11][12][13] The importance of preeclampsia consists of the fact that it is a complication associated with high maternal and fetal morbidity and mortality, mainly in developing countries.…”
Section: Introductionmentioning
confidence: 99%